Hardware Technology of Vision-Based Tactile Sensor: A Review - Zhang, Shixin; Chen, Zixi; Gao, Yuan; Wan, WeiWei; Shan, Jianhua; Xue, Hongxiang; Sun, Fuchun; Yang, Yiyong; Fang, Bin (IEEE sensors journal, 2022)
A vision-based tactile sensor (VBTS) is an innovative optical sensor widely applied in robotic perception. The VBTS consists of a contact module, an illumination module, and a camera module. Its hardware technologies contain preparation, performance, functions, materials, and optimization design of components. However, the current literature lacks a review of hardware technologies to formulate a complete manufacturing scheme. Therefore, this paper focuses on hardware technologies and reviewed the literature over the past five years. We analyze the core components of each module and sort out a technical route. The current challenges and problems of hardware technologies are discussed to propose some feasible solutions. Considering cross-disciplinary applications, we think multidisciplinary hardware technologies are expected to promote the development of next-generation VBTSs. In addition, we aim to provide a valuable guideline for developers to improve the performance of VBTSs.